Job performance and academic excellence of graduates - Hashim, Junaidah (2012)
This paper examines whether or not performance of employees is determined by merit of their academic excellence which is measured by Cumulative Grade Point Average (CGPA). It also measures the variables that could possibly influence employees’ performance; such as job satisfaction, motivation and involvement in co-curriculum activities. The data for this study was obtained from two sources: the supervisors, and the graduate subordinates. An adapted version of questionnaire used by Sarmiento et al. (2007) was utilised to assess the perceived performance of employees. A 13-item scale based on Porter (1964) was used to measure motivation. A 14-item scale based on Hackman and Oldham’s (1975) Job Diagnostic Survey was used to measure job satisfaction. In total, 340 respondents from 87 companies participated in this study. The findings revealed that there is a weak the relationship between performance and CGPA.